Immunospecific albumin microspheres as a drug delivery system for cisplatin and 5-fluorouracil for the treatment of ovarian adenocarcinoma - Truter, Ernest John (Division of Anatomical Pathology, 2017)
Ovarian carcinoma is considered to be the most deadly of the gynaecological malignancies which in its earliest stages is usually asymptomatic. The unsatisfactory survival rates of patients on conventional chemotherapy regimens, necessitates vehicles capable of carrying cytotoxic agents directly to the malignant cells. This mode of targeted delivery allows for efficient tumour cell kill whilst sparing surrounding normal tissue and substantially reducing side-effects. This project examined the possible therapeutic role of a targetable sustained drug delivery system, albumin immunomicrospheres containing the chemotherapeutic agents, cisplatin and 5-fluorouracil, for the treatment of ovarian adenocarcinoma. A rodent cell line, as a model, has proved to be similar to its human counterpart and also has shown to be transplantable from one animal to another. Such a model could therefore be useful for performing experiments relating to drug delivery targetability and therapeutic trials, as well as survival studies, in cases of ovarian adenocarcinoma. In particular, this project examines the efficacy of the immunospecific microspheres containing the drugs in a highly concentrated form, administered intraperitoneally and targeted to an ovarian adenocarcinoma, in an attempt to enhance tumour cell kill whilst largely sparing surrounding normal tissue. It is widely recognized that the effectiveness of most chemotherapeutic drugs would be enhanced if they were to act selectively where they are needed. In order to achieve a therapeutically relevant dose in tumour cells, the amount of drug required usually proves also to be highly toxic to normal tissues. It was postulated that, to overcome the above, it may be feasible to develop a sustained immunospecific drug delivery system to optimize the action of cisplatin and 5-fluorouracil at the target site. With the attainment of the above, it was further postulated that higher doses of drugs could be delivered to the target area effecting higher tumour cell kill, that less normal tissue damage should occur and that toxic side effects of the drugs should be reduced. The rationale for selecting combination therapy of cisplatin and 5-fluorouracil is that, although it has been inferred that DNA intrastrand and interstrand cross-links produced by the cisplatin often repair, this repair can be blocked by 5-fluorouracil by inhibition of thymidylate synthetase, thus preventing DNA strand repair. Albumin immunomicrospheres are relatively innocuous in terms of toxicity, non-antigenic and are capable of accommodating chemotherapeutic agents in a non-specific fashion. We showed that they were capable of a 0. 94% entrapment of 5-fluorouracil and 1.23% cisplatin. Delivery of these drugs at a target site, and at these concentrations, should effect extensive cell kill. As the microspheres are chemically stable and can be manipulated to offload the entrapped drugs satisfactorily, in vitro drug release profiles were performed employing immunospecific microspheres directed towards its target cells. Slow degradation of the drug- containing albumin immunomicrospheres showed that 0.283 μg cisplatin/ml plasma and 0. 799 μg 5-fluorouracil/ml plasma could be made available at the target site over a 14-day period. These concentrations could be maintained over at least another 14 days and effect tumour cell kill satisfactorily. In order to assess the tumour cell kill, we performed clonogenic assays, cell survival growth curves, MTT cytotoxicity assays and assessed the induction of micronuclei in the tumour cells. The synergism between 5-fluorouracil and cisplatin showed a modulation of cisplatin cytotoxicity and total tumour cell kill was achieved at concentrations of 0.5 μg/ml 5-fluorouracil and 0.1 μg/ml cisplat in at the target site. The above-mentioned evidence of effective targeting of the drugs was then investigated in female Wistar rats with ovarian adenocarcinoma to assess comparative survival times when treated with free drugs or immunospecific albumin microspheres containing the drugs. Animals given a free drug dose of 5 mg/kg cisplatin and 20mg/kg 5-fluorouracil, followed by a repeat dose at the same concentrations 7 days later showed that only 14% of the animals survived a 90-day trial period. Animals given an intraperitoneal bolus dose of immunomicrospheres at a dose of 1 O mg/kg cisplatin and 40 mg/kg 5-fluorouracil showed that 60% of the animals survived the 90-day trial period. This data indicated to us that the survival probability of animals treated with drug-containing immunomicrospheres was substantially superior to other protocols employed in this study.